Legal Liability of Pharmaceutical Industry In Consumer Class Action Lawsuits: Analysis of Court Decision Number 771/Pdt.G/2022/Pn Jkt.Pst - Aurelya Putri Alzahrah; Dwi Desi Yayi Tarina (Journal of Law, Politic and Humanities, 2025)
The case of atypical progressive acute kidney injury in children caused by contaminated syrup medicines containing ethylene glycol and diethylene glycol raises legal issues concerning the liability of the pharmaceutical industry. This study analyzes the legal responsibility of pharmaceutical producers and the application of class action mechanisms in Central Jakarta District Court Decision Number 771/Pdt.G/2022/PN Jkt.Pst. The research employs a normative juridical method with statutory and case approaches, using secondary data from legislation, court decisions, and legal literature. The findings show that pharmaceutical industries are obliged to guarantee product safety and quality under Indonesian law, and their negligence gives rise to civil liability enforced through compensation. The class action mechanism proved effective in securing access to justice, procedural efficiency, and legal certainty. This study highlights the need for strict compliance with production standards and the strengthening of class action procedures to enhance consumer protection in Indonesia.